2004
DOI: 10.1007/s00264-003-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiological results of image-based and non-image-based computer-assisted total knee arthroplasty

Abstract: Restoration of the mechanical limb axis and accurate component orientation are two major factors affecting the long-term results after total knee replacement (TKR). Different navigation systems are available to improve the outcome. Image-based systems require pre-operative CT scans, while non-image-based systems gain all necessary information intra-operatively during a registration process. We studied 130 patients who received a TKR either using the CT-based (Knee 1.1) or the CT-free module (CT-free Knee 1.0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 18 publications
(27 reference statements)
2
45
0
2
Order By: Relevance
“…Although many studies have confirmed this theory [1,3,9,24,39], others have shown that there is no difference in orientation or alignment of the femoral or tibial components than that achieved by conventional methods [12,22,23,42]. When evaluating the published reports on navigation knee arthroplasty, two important factors limit comparisons among clinical series.…”
Section: Alignmentmentioning
confidence: 87%
See 2 more Smart Citations
“…Although many studies have confirmed this theory [1,3,9,24,39], others have shown that there is no difference in orientation or alignment of the femoral or tibial components than that achieved by conventional methods [12,22,23,42]. When evaluating the published reports on navigation knee arthroplasty, two important factors limit comparisons among clinical series.…”
Section: Alignmentmentioning
confidence: 87%
“…However, the extent of malalignment below which good clinical results are expected is not known [21]. Many studies have shown that placement of components within ±3°of the mechanical axis reduces the risk of early loosening [1,5,11] whilst other studies have shown this threshold to be higher [14,21,41].…”
Section: Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our objectives were: (1) to evaluate the strength of the association between standard pre-and postoperative radiographic and intraoperative navigation alignment measurements; (2) to determine the potential sources of error inherent to the process of radiographic and navigated alignment assessment; and (3) to examine the subtle differences that exist between desired alignment (anteroposterior [AP] mechanical axis and sagittal tibial and femoral axes of 0°) and clinically accepted alignment (final alignment after the bone cuts were made and implants placed) as assessed through an intraoperative navigation system.…”
Section: Introductionmentioning
confidence: 99%
“…These systems provide the opportunity to improve the accuracy of component orientation and restoration of the mechanical leg axis [3,12,17]. Using the computer-assisted technique, intraoperative angular and distance measurements have become available, with an accuracy of less than 1°or 1 mm [7].…”
Section: Introductionmentioning
confidence: 99%